Evaluation of the enantioselectivity of new chiral ligands based on imidazolidin-4-one derivatives - Bartáček, Jan; Chlumský, Karel; Mrkvička, Jan; Paloušová, Lucie; Sedlák, Miloš; Drabina, Pavel (Beilstein-Institut, 2024)
The new chiral ligands I-III based on derivatives of imidazolidin-4-one were synthesised and characterised. The catalytic activity and enantioselectivity of their corresponding copper(II) complexes were studied in asymmetric Henry reactions. It was found that the enantioselectivity of these catalysts is overall very high and depends on the relative configuration of the ligand used; cis-configuration of ligand affords the nitroaldols with major enantiomer S- (up to 97% ee), whereas the application of ligands with transconfiguration led to nitroaldols with major R-enantiomer (up to 96% ee). The ""proline-type"" ligand IV was also tested in asymmetric aldol reactions. Under the optimised reaction conditions, aldol products with enantioselectivities of up to 91% ee were obtained.
Hodnocení enantioselektivity nových chirálních ligandů na bázi derivátů imidazolidin-4-onu
Keywords: asymmetric aldol reaction; Henry reaction; chiral ligands; enantioselective catalysis; imidazolidine derivatives; asymetrická aldolová reakce; Henryho reakce; chirální ligandy; enantioselektivní katalýza; imidazolidinové deriváty